PENERAPAN MODEL PEMBELAJARAN CIRC UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS IV - Nur Ilmi; Faharuddin, Nurfadhilah; Muhammad Asrul Sultan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on the literacy skills of class IV students. This study question is how to implement a learning model in class IV UPT UPT State Elementary School 202 Pinrang. The purpose of this research is to determine the process and results of implementing CIRC learning models in improving the literacy skills of reading class IV students’ understanding. This research approach is a qualitative approach. The type of research used is Class Action Research (PTK). Data were collected through observations, dokumentas, and tests. Data is processed through data condensation, data presentation, and drawing conclusions. The subject of this study were 18 people consisting of 1 teacher and 17 class IV students. The results show that learning on the I cycle gets sufficient value (C), but these results do not yet meet standards. The results of research on cycle learning II show good value (B) which where student activity is in high qualifications. The conclusion of the results of this study indicate that the application of a learning model of CIRC can increase the literacy skills of grade IV students in UPT SD Negeri 202 Pinrang.